Keabsahan Perkawinan Ngerorod (Kawin Lari) di Desa Kelusa, Kabupaten Gianyar - I Wayan Bayu Suta; I Nyoman Putu Budiartha; I Ketut Sukadana (Fakultas Hukum, Universitas Warmadewa, 2021)
Today's Balinese customary law recognizes two ways to carry out a marriage, namely marrying by memadik (engaging) and marrying by means of Ngerorod (kawin lari). If during the engagement period the parents and families of both parties have the blessing, the marriage will be done by memadik. Conversely, if the engagement period does not get the blessing of the parents and family of one or both parties, while the couple has already fallen in love and it is no longer possible to be separated, then ngerorod is the only way to get married. This study aims to determine the validity of the Ngerorod marriage (kawin lari) in the village of Kelusa, and to determine the legal settlement of the Ngerorod marriage in the village of Kelusa. The research method used is an empirical legal research method with a sociology of law approach. The results showed that the legality of the ngerorod marriage that usually occurs in Kelusa village is that the man and the woman make a statement that the woman is legally in the house of the man she loves. The male family came to Bendesa Adat and Kelian Adat to discuss the ngerorod marriage, then the man picked up the woman in front of her house. Then, the legal settlement in the Ngerorod Marriage in Kelusa village was because the woman was still married to another person, after going through a sangkep (meeting) by the traditional village prajuru giving customary sanctions and being directed or obliged to legally divorce according to the provisions of the Law.